Henry Tonks and the true face of war - Fusco, Roberta; Tesi, Chiara; Larentis, Omar; Tonina, Enrica (Medicina Historica, 2021)
Wounded faces, deformed, sewn up, assembled. This is the most visible legacy and at the same time the one that no one wants to see of every conflict. Reconstructive plastic surgery was born one hundred years ago during the First World War. Millions of people died, but millions more were severely injured. The trenches of World War I protected the bodies from shrapnel, but not faces. Thus was born the need to reconstruct faces using other parts of the body. Surgeon D. Gillies applied his knowledge of reconstructive surgery in a creative and innovative way to treat severely mutilating facial injuries. Alongside him, the painter and physician Henry Tonks was tasked with making pastel drawings of the facial injuries of wounded soldiers before and after surgery. Through this collaboration with Gillies, Tonks produced a series of portraits of facial injuries that remains unsurpassed to this day for emotional impact, scientific interest, and subtlety of representation